PERANCANGAN DAN IMPLEMENTASI WEBSITE PROFIL SEKOLAH DI SEKOLAH ADVENT MISSION SAGULUNG MENGGUNAKAN WORDPRESS DAN MYSQL - Kelven Liong; Muhamad Dody Firmansyah (P3M Institut Teknologi Pagar Alam, 2022)
The Sagulung Adventist Mission School is one of the schools that was established in 2007, the school still does not have a school profile website, school activities in conveying information are still through teachers who teach in class so there is a possibility of miscommunication between teachers and parents. The methodology used in this study is applied research that aims to solve the problems faced by Adventist Mission Sagulung in this digital era. One of the basic needs for society is the availability of education. Data collection techniques are interviews and observation. Interviews were conducted with the school administration and observations by observing the needs of the school. The method used in making the website is the Software Development Lifecycle (SLDC) method, namely the waterfall model. Contribution to this research is to help disseminate information, both news and announcements through the school website that has been created by the author. The purpose of this study was to design an information system based on the Sagulung Adventist Mission school website. The results of this study indicate that the use of a website-based information system can be a Publication Revolution in opening a wider range of school information to convey various types of information about the school, providing convenience in academic activities, eliminating time, distance and place restrictions as obstacles to students, parents, and the community who want to find information about the school. The results of the research are in the form of a school website called